2010
DOI: 10.2501/s026504871020135x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of surfer/seeker mode on the effectiveness of website characteristics

Abstract: This research examines how two commercial website design variables, visual complexity and source of interactivity control, are more or less effective depending on a consumer's purpose for visiting a website (consumer user mode). An online experiment was conducted in singapore utilising over 70 experimental mock web pages. The authors find that goal-directed seekers prefer a consumer-controlled interactive environment as well as a visually simple design, whereas experiential surfers prefer marketer-controlled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The telic/paratelic states are mutually exclusive. It is related to the degree of feeling arousal, and these two states will affect the attitude and feelings of the individual in different ways (Stanaland & Tan, 2010). For example, an individual is serious-minded, goal-oriented, and arousalavoidant in telic states.…”
Section: Reversal Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The telic/paratelic states are mutually exclusive. It is related to the degree of feeling arousal, and these two states will affect the attitude and feelings of the individual in different ways (Stanaland & Tan, 2010). For example, an individual is serious-minded, goal-oriented, and arousalavoidant in telic states.…”
Section: Reversal Theorymentioning
confidence: 99%
“…They are in low felt arousal and prefer relaxation and calmness. Once the high felt arousal happened, they may feel anxious and angry (Stanaland & Tan, 2010). Therefore, in addition to the content related to the topic, other messages are aware of disturbing with the goal achievement and reduce the attention towards peripheral stimulation (Janiszewski, 1998).…”
Section: Reversal Theorymentioning
confidence: 99%
“…Laboratory experiments manipulate consumers' goals (surfing the web vs. seeking information) to demonstrate that banner characteristics, such as size and animation, are more or less effective depending upon consumers' goals (Li and Bukovac 1999;Stanaland and Tan 2010).…”
Section: Banner Advertising -Current Practicementioning
confidence: 99%
“…In fact, Westerik et al (2006) calls the approach the ''standard perspective'' for studying audience activity (p. 140). In the case of internet usage, early studies suggested that motivations such as information seeking, entertainment, and socializing may drive the choice of online media as well as influence associated attitudes and behaviors that fulfill motivational needs (Yoo, 1996), with more recent work showing that consumer motivation for going online influences consumer preference for a site's visual complexity and degree of consumer navigational control (Stanaland and Tan, 2010). ''Gratifications,'' which are reasons for media use (Veikko, 2005), have been identified in a variety of media settings, including entertainment and information among young adults using social networks (Urista et al, 2011),personal utility and social utility among adults watching reality television programming (Barton, 2009), and status and concentration (among others) for users of MP3 players (Zeng, 2011).…”
Section: Usage Motivations Privacy Concerns and Disclosurementioning
confidence: 99%